FACTORS ASSOCIATED WITH URETHROCUTANEOUS FISTULA COMPLICATION IN HYPOSPADIAS PATIENT AFTER URETHROPLASTY IN FATMAWATI GENERAL HOSPITAL: A RETROSPECTIVE COHORT DESIGN - Hidianingsih, Septiani; Hutasoit, Yonas Immanuel (Indonesian Journal of Urology, 2022)
Objective: This study compared several factors that are thought to contribute to the incidence of complications of urethroplasty fistula after urethroplasty, including meatus location, degree of chordee, surgical technique, and postoperative stent type. Material & Methods: This study is an analytical study with retrospective cohort design. After adjusting to the inclusion and exclusion criteria, 89 subjects with proximal hypospadias were subjected to urethroplasty at Fatmawati General Hospital, Jakarta from 2016 to 2019. An analysis of the relationship between several variables and the incidence of uretrocutaneous fistula was analyzed. Results: There was no significant difference between the one-stage and two-stage urethroplasty technique on the incidence of urethrocutaneous fistula (p = 0.063). There was no significant difference between the degree of chordee and complications of urethrocutaneous fistula after urethroplasty (p = 0.677). The relationship between the use of silastic stent, catheter, or cystostomy type was also not significant in complications of urethrocutaneous fistula (p = 0.576). The location of the urethral meatus also did not have a significant role in predicting the incidence of post-urethroplasty urethrocutaneous fistula (p = 0.169). Conclusion: Surgical technique (one stage and two stages), type of stent, degree of chordee, and location of the urethral meatus, did not have a significant correlation with the incidence of urethrocutaneous fistula in hypospadias patients after urethroplasty.